Characterizing gait asymmetry via frequency sub-band components of the ground reaction force. (April 2015) - Su, B.L.; Song, R.; Guo, L.Y.; Yen, C.W.
Highlights: We develop ground reaction force (GRF) based asymmetry measure for human gait. Features extracted from GRF can characterize different gait patterns. The measure is derived from the frequency sub-band components of the GRF. The proposed asymmetry measure can be used to detect Parkinson's disease. Abstract: This study introduces gait asymmetry measures by comparing the ground reaction force (GRF) features of the left and right limbs. The proposed features were obtained by decomposing the GRF into components of different frequency sub-bands via the wavelet transform. The correlation coefficients between the right and left limb GRF components of the same frequency sub-band were used to characterize the degree of bilateral symmetry. The asymmetry measures were then obtained by subtracting these coefficients from one. To demonstrate the effectiveness of these asymmetry measures, the proposed measures were applied to differentiate the walking patterns of Parkinson's patients and healthy subjects. The results of the statistical analyses found that the patient group has a higher degree of gait asymmetry. By comparing these results with those obtained by conventional asymmetry measures, it was found that the proposed approach can more effectively distinguish the differences between the tested Parkinson's disease patients and the healthy control subjects.